HUBUNGAN PENGETAHUAN DENGAN SIKAP IBU TENTANG PELAKSANAAN METODE KANGGURU PADA BAYI BBLR - Widianti, Sherly; Sukma , Tiara (Jurnal Kesehatan dan Pembangunan, 2025)
According to data from the World Health Organization (WHO) in 2023, the infant mortality rate was recorded at 16.85 per 1,000 live births. One of the main causes of neonatal mortality is the birth of babies with low birth weight (LBW). One method that can be used to handle LBW babies is the kangaroo method. The success of implementing this method is influenced by various factors, including the knowledge and attitude of the mother. This study aims to identify the relationship between the level of knowledge and attitudes of mothers towards the implementation of the kangaroo method on LBW babies in the Neonatal Ward of Siti Fatimah Azzahra Hospital, South Sumatra Province, in 2024. This study uses a quantitative analytical approach with a cross-sectional design. The study population included all mothers who gave birth to LBW babies in the neonatal ward of the hospital, with a sample size of 25 respondents selected through purposive sampling techniques. Data analysis was carried out using the Chi-Square statistical test. The results of the study showed a significant relationship between maternal knowledge (p-value = 0.028) and maternal attitude (p-value = 0.007) with the implementation of the kangaroo method in LBW babies. As a recommendation, the results of this study are expected to be a consideration for hospitals in improving the quality of health services, especially in the implementation of care using the Kangaroo Method.